Thermoelectric Conversion Performance of Combined Thermoions System for Space Nuclear Power Supply - Zhang, Haochun; Yin, Dezhuang; Chai, Xiaoming; Kong, Boran; Liu, Xiuting (Frontiers in Energy Research, 2020)
Thermoelectric conversion system, as one of the keys of space nuclear power supply system, is of great significance to the development and application of space nuclear power source. Thermion thermoelectric conversion system is a kind of thermoelectric conversion technology with potential for development, it has simple equipment and compact structure, but its conversion efficiency is limited by the inherent characteristics of the heat ion Energy converter, in order to improve the conversion efficiency of the thermionic energy converter, the thermionic energy converter and thermoelectric generator are coupled. In this paper, the thermionic-thermoelectric generator is taken as the research object, and the thermodynamic analysis and calculation of the thermionic-thermoelectric generator model is carried out by using the existing formula, on the basis of which the appropriate parameters are selected to optimize the system performance.